Bcl-2 inhibition in the treatment of hematologic malignancies - Wei, John X.; Konopleva, Marina (Frontiers in Hematology, 2023)
Apoptosis is a tightly regulated process of cell death occurring through extrinsic and intrinsic pathways (1). The Bcl-2 family of proteins is implicated in the intrinsic pathway and encompasses both pro-apoptotic and anti-apoptotic proteins. Anti-apoptotic Bcl-2 proteins are frequently overexpressed in hematologic malignancies and so Bcl-2 inhibitors have been developed to combat these malignancies. The first and so-far only FDA-approved Bcl-2 inhibitor has been venetoclax, initially for treatment of chronic lymphocytic leukemia (CLL) with 17-p deletion as a second-line agent, followed by later expansion to all CLL and selected acute myeloid leukemia (AML) indications. Venetoclax and inhibitors of other Bcl-2 family members have demonstrated significant potential. However, their use requires careful consideration of disease indication, along with biomarkers associated with disease and optimal drug combinations (2). Side-effect profiles and specific patterns of resistance must be considered as well. In this review, we examine in detail the characteristics of the Bcl-2 family of proteins and their role in apoptosis. We discuss the drug development process that led to the first-in-class approval of venetoclax, along with relevant use considerations. Finally, we examine future directions in this domain of pharmaceutical development.